Effectiveness of Self Instructional Module (SIM) on Knowledge and Attitude Regarding Care of Attempted Suicide Patients among Staff Nurses – A Pre Experimental Study - Raman Deep; KVS Chaudhary; Harsha Mary Chacko (Institute of Medico-legal Publications Pvt Ltd, 2021)
Suicide is a major public health problem and one of the leading causes of deaths worldwide. The effectsof suicide go beyond the person who acts to take his/her life; it can have lasting effect on family, friendsand communities. The role of a nurse specific to suicide prevention includes both system and patient levelinterventions.Objectives of the study:· To assess the existing knowledge and attitude regarding care of attempted suicide patients among staffnurses.· To evaluate the effectiveness of self –instructional module regarding care of attempted suicide patientsamong staff nurses.· To find out the association of post -test knowledge and attitude regarding care of attempted suicidepatients among staff nurses with selected demographic variables.Materials and Methods: In this pre- experimental research study non probability convenient samplingtechnique was used to select 60 staff nurses from selected Hospitals. A self- structured questionnaire andattitude scale was used to assess the knowledge and attitude of the staff nurses regarding the care of attemptedsuicide patients.Result: The finding of the study revealed that majority 95% (57)of staff nurses had moderate knowledge andonly 5% (3) had inadequate knowledge regarding care of attempted suicide patients in pre-test. After goingthrough Self Instructional Module, 83.37 % (50) of the staff nurses had adequate knowledge and 16.66% (10)had moderate knowledge regarding care of attempted suicide patients. The attitude scale findings revealedthat 100% (60)of staff nurses had neutral attitude regarding care of attempted suicide patients in pre-test andin post-test 100%(60) had positive attitude regarding care of attempted suicide patients.Conclusion: Study concludes that going through Self-Instructional module helps method in improvingknowledge and attitude of the staff nurses regarding care of attempted suicide patients.